DEVELOPMENT OF LKPD MATERIAL ON BASIC SERVICE TECHNIQUES IN VOLLEYBALL IN GRADE VIII OF NAPALLICIN STATE MIDDLE SCHOOL - Yohana Oktapia; Muhammad Suhdy (Teaching and General Education Studies, 2026)
This study aims to develop a Student Worksheet (LKPD) on the basic service technique in volleyball for eighth-grade students at SMP Negeri Napallicin using the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. This research is a type of Research and Development (R&D). The validity results showed that the LKPD was in the "very valid" category with an average score of 0.90, based on assessments from a media expert (0.9), a language expert (0.92), and a material expert (0.9). The practicality of the LKPD was tested through one-to-one, small group trials, and teacher responses, resulting in an average practicality percentage of 83.44%, categorized as very practical. The effectiveness test was conducted by administering pretests and posttests to 20 students, with an average pretest score of 34.75 and a posttest score of 82.75. The N-gain score of 0.73 indicated a high category of learning improvement. Therefore, the LKPD on the basic service technique in volleyball is considered valid, practical, and effective for use in the learning process.